IMPLEMENTASI PROGRAM CAR FREE DAY DI KOTA SEMARANG - Robeth Husein; Aufarul Marom; R. Slamet Santosos (Journal of Public Policy and Management Review, 2014)
The problems such as lack of public awareness of the city of Semarang on the environment particularly concerning air pollution and lack of public participation in in the program Car Free Day would be a background of this research. This research was meant to find out how the implementation of the program Car Free Day in the town of Semarang and knowing factor - factor thruster and inhibitors in the program Car Free Day. This research using methods research qualitative descriptive. The subjects in this study consisted of six ( 6 ) informant main. The results showed that the implementation of the programme of Car Free Day in the city of Semarang have yet to demonstrate the effective implementation. The success of the goals enshrined in the rules of the Mayor of Semarang number 22 year 2011 free days on the implementation of the motor vehicle has not been fully achieved, Car Free Day programs that aim to restore the quality of the air in fact only recently able to reduce air pollution. The participation of the community in Semarang city are still without wind in the implementation of the program should be Car Free Day could be more enthusiastic and regularly follow this activity so that an open space for the public this is true can actually manifest properly. Changes in mindset and behaviour of society not Semarang City shows what kind of behavior expected by the executor. Nevertheless the executing this program already has expertise and competence in accordance with the programme of Car Free Day since leading from this program comes from the background environment. Based on these conclusions, the researchers recommend to the executing program Car Free Day this need high commitment and support from the Government as well as society Semarang city, especially the parties involved to implement the program of Car Free Day an ongoing basis in order to achieve the purpose of which is to restore the quality of the air in Semarang city.